(untitled) (ENTRENOVA - ENTerprise REsearch InNOVAtion Journal, 2025)
Leadership is one of the functions of management, and unlike other management functions, it cannot be partially transferred to others, so leadership becomes the most important and real function of management. It is a ubiquitous and current topic because successful leadership is a skill that is present in different aspects of life and organizations, such as in a company, the state, in wars, or within the family. The art is to influence other people and relationships so that they are willing to achieve set goals. Leadership is an action, not a position that is automatically gained by a position in an organization. The phenomenon of leadership and successful leaders always capture the attention of not only the scientific but also the social public. Given the large number of studies conducted and studies written on the importance and the impact of leadership, numerous models, approaches, and leadership theories have been formed. The paper aims to shed some light on the research trends of leadership types in scientific literature. The Scopus database has been researched using the keywords “leadership type”, which resulted in 127 journal articles. A bibliographic analysis has been conducted with the focus on the timeline of publications, trends in leading authors, institutions, and countries, and the financing institutions analysis. Citation analysis has also been conducted with the focus on papers with the highest number of citations. Topics of the papers have been analyzed using the text mining analysis, which revealed a variety of management-related topics.